0121 Overcoming Barriers To Simulation; Low Cost, High Fidelity. (1st November 2014) - Davies, Victoria
Abstract : Background: In units where simulation is still relatively new, common barriers to simulation include fidelity of the models and the high costs involved. Development of increasingly high fidelity simulators has been one way of overcoming learners' issues with realism. These highly technological manikins have wow factor and are hugely popular, however they come with a hefty price tag. This may lead to the association of simulation as a costly endeavour and therefore not an affordable training modality for units with financial constraints. Description: At Leeds children's hospital we run regular multidisciplinary neonatal simulation. In our experience we found that with some creativity and resourcefulness, it is possible to create simple effective touches that add realism and draw candidates in for deeper experiential learning. Where we used low fidelity set up, on average candidates ranked the realism 4.3 (5-point Likert Score). Improvements: We share several novel ways to add fidelity to simulation whilst maintaining fiscal restraint. Low fidelity newborn manikin covered with mint sauce, externally and into oropharynx, to mimic troublesome meconium in newborn. Hand newborn baby wrapped in wet towel and create draft in room by keeping window open. Discuss environmental thermoregulation at birth. 'Gastroschisis bowel' from a combination of redcurrant jelly enveloped in sausage skin. (Can be freezed and reused) Simulation app with iPhone monitor, to recreate sound effects from real monitors. Laminated drug charts with wipe-off pens, to avoid throwing out drug charts after every scenario. Take home message: There is evidence to support that simulation does not need to be costly and highly technological for it to be beneficial. 1 We encourage more widespread sharing of these simple novel ideas so simulation is not reserved for departments with simulation centres and expensive models, but made accessible to units with low budgets and highly ingenious ideas. Reference: Norman G, Dore K, Grierson L. The minimal relationship between simulation fidelity and transfer of learning. [Review] Medical Education 2012;46(7):636–47